2019
DOI: 10.1093/hmg/ddz197
|View full text |Cite
|
Sign up to set email alerts
|

Over 1000 genetic loci influencing blood pressure with multiple systems and tissues implicated

Abstract: High blood pressure (BP) remains the major heritable and modifiable risk factor for cardiovascular disease. Persistent high BP, or hypertension, is a complex trait with both genetic and environmental interactions. Despite swift advances in genomics, translating new discoveries to further our understanding of the underlying molecular mechanisms remains a challenge. More than 500 loci implicated in the regulation of BP have been revealed by genome-wide association studies (GWAS) in 2018 alone, taking the total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 85 publications
0
36
0
1
Order By: Relevance
“…In humans, recent progress in large-scale genome-wide association studies (GWASs) has succeeded in the identification of over 1000 genetic loci influencing BP ( Cabrera et al, 2019 ). Despite the large number of loci, the genetic variance explained by all loci in aggregate remains low (at most 5.7% of BP variation), indicating that individual common variants mostly exert weak effects on BP.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, recent progress in large-scale genome-wide association studies (GWASs) has succeeded in the identification of over 1000 genetic loci influencing BP ( Cabrera et al, 2019 ). Despite the large number of loci, the genetic variance explained by all loci in aggregate remains low (at most 5.7% of BP variation), indicating that individual common variants mostly exert weak effects on BP.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the association between rs13107325 and putamen volume found it to be accompanied by decreased SLC39A8 expression in the putamen and with the SNP-trait association decreased in those with schizophrenia 33 . The rs13107325 SNP has also been associated with schizophrenia itself 23 , neurodevelopmental outcomes and intelligence test performance 34,35 , blood pressure 36 and numerous other factors 13,37,38 , including over 70 anthropometric traits (http://www.nealelab.is/uk-biobank/). The rs1800562 HFE SNP is also known as Cys282Tyr and has been associated with reduced putamen volume and T2star signal in the striatum 13 , as well as being involved in iron regulation and transport, being a major risk variant for hemochromatosis where it accounts for approximately 85% of cases 39 , mineral metabolism and haematological disorders 40 13 with VCAN, which encodes the extracellular matrix protein Versican and which plays a number of crucial roles in maintaining the extracellular matrix, including in nervous system development 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) have identified over 1000 genetic loci influencing blood pressure with multiple systems and tissues implicated [9]. Common variants are widely accepted to have effect on complex disease.…”
Section: Taking Into Account the Impact Of Rare Variants On Complex Dmentioning
confidence: 99%